Synthesisof silver nanoparticles by some locallyLactobacillus spp.and detection of their antibacterial activity - Jehan Abdul Sattar Salman (College of Pharmacy / Mustansiriyah University, 2013)
The study included the rapid synthesis and antibacterial activity of silver nanoparticles synthesized by locally Lactobacillus spp.(Lactobacillus acidophilus, L. gasseri, L. rhamnosus, L. fermentum). The silver nanoparticles were characterized with Atomic Force Microscopy (AFM) and found theaverage size ranges from 33.71 to39.16 nm. Finally antibacterial activities of the silver nanoparticles were checked against pathogenic bacteria (Escherichia coli, Acinetobacter baumannii, Staphylococcus aureus and Listeria monocytogenes). The zone of inhibiton seems extremely good showing a relatively large zone of inhibition in both gram positive and gram negative bacterial isolates. To the best of our study this is the first report on synthesis of silver nanoparticles by locally Lactobacillus spp.